2011
DOI: 10.1111/j.1440-1800.2011.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Reframing caring as discursive practice: a critical review of conceptual analyses of caring in nursing

Abstract: This study critically examines the way in which the concept of caring is presented in the nursing literature through conceptual analytic approaches. A critical reflection on the potential consequences of representing a concept of caring as vague and ambiguous, yet central to ontology and epistemology in professional nursing is presented drawing on comparisons between the conceptual analyses of caring, and of structuralist perspectives of language, and how this potentially limits scholarship in this area. A sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 51 publications
(92 reference statements)
0
35
0
Order By: Relevance
“…According to some authors, this is because for years nursing theory has claimed care as the central axis of nursing practice (Sargent 2012). Nonetheless, its definition remains complex and ambiguous (Khademian & Vizeshfar 2008, Sargent 2012.…”
Section: Care and Its Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to some authors, this is because for years nursing theory has claimed care as the central axis of nursing practice (Sargent 2012). Nonetheless, its definition remains complex and ambiguous (Khademian & Vizeshfar 2008, Sargent 2012.…”
Section: Care and Its Implementationmentioning
confidence: 99%
“…According to some authors, this is because for years nursing theory has claimed care as the central axis of nursing practice (Sargent 2012). Nonetheless, its definition remains complex and ambiguous (Khademian & Vizeshfar 2008, Sargent 2012. Alberdi (1992) has shown that in spite of the focus on care in definitions of nursing, providing care continues to be difficult in practice because of an overload of tasks related to procedures, diagnosis or equipment (Lleixá et al 2009).…”
Section: Care and Its Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Self efficacy is an important factor that determines the the capacity of any individual involved in the nursing profession. Not only this, high self efficacy improves the quality of care delivered and is a crucial factor in improving the performance of any individual in an organization (Sargent 2011). Although, it is well known that empathy is an essential requirement in nursing profession, it is a concept that is still masked in quite a lot of ambiguity as well as controversy among the medical and social scholars.…”
Section: Literature Review 31 Nursing-roles and Responsibilitiesmentioning
confidence: 99%
“…The conceptual properties and dimensions of caring have been described somewhat differently in the literature and a consensus conceptual definition is yet to be established (Sargent ). Morse et al .…”
Section: Introductionmentioning
confidence: 99%